Giant cellulitis-like Sweet syndrome with myofasciitis: Multimodality imaging findings and streptococcal trigger - Zi-Ning Choo; Verena Isak; Elisha M. Singer; Joanna Harp; Alison Schonberger; Michael L. Miller; Cynthia Magro; Roger J. Bartolotta (Radiology Case Reports)
Sweet syndrome is a rare neutrophilic dermatosis that can mimic infectious cellulitis. In this case, a 34-year-old woman presented to the emergency department with fever, leukocytosis, and painful erythematous right thigh plaque. She was initially started on broad-spectrum antibiotics for presumed cellulitis, but worsening systemic symptoms (including hypotension) and right thigh MR findings of myofasciitis raised concern for necrotizing soft tissue infection with systemic inflammatory response syndrome. Right thigh fasciotomy was performed, but all tissue sampling and cultures remained negative for infection. Subsequent CT and ultrasound of the right thigh revealed early myonecrosis in the setting of inflammatory myofasciitis. Skin biopsy showed papillary dermal edema and extensive interstitial neutrophilia with leukocytoclasia without microbial pathogens, consistent with a diagnosis of giant cellulitis-like Sweet syndrome. Treatment with high dose intravenous corticosteroids produced rapid clinical improvement. This case describes a rare presentation of Sweet syndrome with muscle involvement, outlines diagnostic features in the multimodality imaging of neutrophilic myofasciitis, and underscores the importance of considering Sweet syndrome in soft tissue inflammation that is unresponsive to antimicrobial therapy.